ANALISIS KREDIT, GDP, INFLASI DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI - Yusri Hazmi (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
The economic development is closely related to the role of the banking sector. In a crisis condition, the role of banking institutions is less than optimal so that the impact on disturbed national economy. When the economy stagnated the banking sector is also affected, so the intermediation function is not normal. Credit has a positive causality relationship with economic growth. This research is to know the causality relationship between credit, GDP, Inflation and Interest Rate to Economic Growth. The method used is VAR / VECM. Test the Granger causality. VECM estimates show that economic growth positively affects credit, while inflation and lending rates have a negative effect. Keywords: Credit, PDB, inflation, interest rate and economic growth